ADHD pharmacogenetics across the life cycle: New findings and perspectives. Issue 4 (8th May 2014) - Bruxel, Estela Maria; Akutagava‐Martins, Glaucia Chiyoko; Salatino‐Oliveira, Angelica; Contini, Verônica; Kieling, Christian; Hutz, Mara Helena; Rohde, Luis Augusto
<x xml:space="preserve">Abstract</x> Attention‐deficit/hyperactivity disorder (ADHD) is a complex and heterogeneous disorder, affecting individuals across the life cycle. Although its etiology is not yet completely understood, genetics plays a substantial role. Pharmacological treatment is considered effective and safe for children and adults, but there is considerable inter‐individual variability among patients regarding response to medication, required doses, and adverse events. We present here a systematic review of the literature on ADHD pharmacogenetics to provide a critical discussion of the existent findings, new approaches, limitations, and recommendations for future research. Our main findings are: first, the number of studies continues to grow, making ADHD one of the mental health areas with more pharmacogenetic studies. Second, there has been a focus shift on ADHD pharmacogenetic studies in the last years. There is an increasing number of studies assessing gene–gene and gene–environment interactions, using genome‐wide association approaches, neuroimaging, and assessing pharmacokinetic properties. Third and most importantly, the heterogeneity in methodological strategies employed by different studies remains impressive. The question whether pharmacogenetics studies of ADHD will improve clinical management by shifting from trial‐and‐error approach to a pharmacological regimen that takes into account the individual variability remains unanswered. © 2014 Wiley Periodicals, Inc.